Pengaruh Elektronik Absensi dan Perilaku Cyberloafing Terhadap Produktrivitas Karyawan Studi Empiris Pada PT.Pertamina Kantor Cabang Sukabumi - Lestari Damayanti; Nor Norisanti; Resa Nurmala (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to determine the effect of electronic attendance and cyberloafing behavior on employee productivity. The method to be used in this research is to use quantitative research methods with descriptive and associative approaches. Data collection tehniques that will be used by researchers include observation, interviews, questionnaires, and literature studies. The sample of respondents who will be used by the researcher is 32 respondents from the employees of PT.Pertamina, Sukabumi Branch Office. The data analysis technique and is assisted by using the Statistical Product and Service Solution, SPSS. Software. In this study it can be seen that partially, the electronic variables of absenteeism (X1) and cyberloafing behavior (X2) each have a significant effect on employee productivity (Y). simultaneously, electronic attendance (X1) and cyberloafing behavior (X2) have a significant effect on employee productivity (Y). the coefficient value of R2 by looking at the R square value of 0,792 or 80,5%. Keywords: employee productivity; electronic attendance; cyberloafing behavior